The role of inflammatory markers in the diagnosis and follow-up of diabetic foot osteomyelitis (Annals of Medical Research, 2021)
Aim: Diabetic foot infections are a major cause of mortality and morbidity in diabetic patients. These mortality and mortality rates increase further when osteomyelitis develops. Simple techniques are needed to facilitate the diagnosis and follow-up of diabetic foot osteomyelitis. Material and Methods: Eighty-nine patients who underwent amputation due to diabetic foot between January 2012 and May 2017 were included in the study. The patients were grouped as those with or without osteomyelitis according to their pathology results. C-reactive protein (CRP) level and erythrocyte sedimentation rate (ESR) were assessed pre- and postoperatively.Results: Preoperative ESR values were significantly higher in the osteomyelitis group (p0.05). Comparison of preoperative, postoperative 2-week, and postoperative 1-month ESR values showed a statistical difference among all time points (p0.05), with lower postoperative values compared to preoperative values. At a cut-off value of 55.5 mm/h, preoperative ESR had sensitivity of 95.3% and specificity of 87.5% in the discrimination of patients with and without osteomyelitis.Conclusion: ESR is a simple, rapid, and cost-effective diagnostic marker with high sensitivity and specificity in the diagnosis of diabetic foot osteomyelitis. However, monitoring CRP values may be superior to ESR when evaluating early treatment response.
Keywords: C-reactive protein; diabetic foot infections; erythrocyte sedimentation rate; osteomyelitis